Enhancing academic performance of business students using generative AI: An interactive-constructive-active-passive (ICAP) self-determination perspective - Gao, Ziyi; Cheah, Jun-Hwa; Lim, Xin-Jean; Luo, Xi (Elsevier, 2024)
Generative artificial intelligence (GAI) tools, such as ChatGPT, have emerged as valuable assets in higher education. Despite their potential benefits in academic support, questions persist about the concrete advantages of integrating this technology into learning processes and its impact on academic outcomes. This research addresses this gap by investigating the influence of technology integration on academic performance, employing the Interactive-Constructive-Active-Passive (ICAP) framework and self-determination theory. The empirical findings from Chinese business students using Wenjuanxing platform reveal a positive impact of technology integration on business students' motivation, encompassing their learning desires, self-efficacy, and future beliefs, ultimately leading to enhanced academic performance. Notably, while epistemic curiosity augments the effects of technology integration on learning desires and future beliefs, its influence on self-efficacy is not significant. This suggests that curiosity alone might not be enough to alter deeply ingrained beliefs about one's capabilities. In conclusion, this study underscores the academic significance of these findings and their practical implications for educators and business students in optimizing ChatGPT's potential for academic success.